ANALYTICAL DECISION SUPPORTING SYSTEMS FOR FORMATION AND MAINTENANCE OF STATE TARGETS PROGRAMS OF PRIORITY DIRECTIONS OF UKRAINE’S DEVELOPMENT - Bocharnikov, V. P.; Yatsishin, Yu.V. (Problems of Informatization and Management, 2021)
An approach to information and analytical support for the formation and maintenance of state target programs, based on the theory of fuzzy measures and fuzzy-integral calculus, and allows to create models of fuzzy processes, taking into account various uncertainties.